Rol que desempeñan los medios digitales locales y su influencia en los estudiantes de quinto semestre de la carrera de Comunicación Social de la Universidad Técnica de Babahoyo - Posligua Guayamabe, Evelyn Nathali (2018)
The aim of the research work is to analyze the digital means of communication and define how they manage to influence young students in a specific way in the career of Social Counseling. To make this analysis a reference is made of its incidence within the teaching-learning process of this university degree, as well as outside of it, that is, it is intended to make a thorough study on several aspects that are affected in several ways by these common tools that today have become essential. The university community that made up the population had an active participation in the execution of this research and declared their intentions to know about these media and their influence and how to make use of them as resources within the activities that in the professional training field exist , the population is aware of the usefulness and relationship between these communicative tools and to act as a student of social communication, in this way it would favor meaningful and competent learning in the student. The development of this research work yielded good results since it aroused the interest of the students to use in addition to those already known, other useful tools such as digital media, curiosity was also raised about knowing these media and motivated those involved about the importance of improving day by day in the professional performance as information workers, learning about these means requirements of a technologically globalized world and united by the internet. The learning process in the students who would be the most benefited would have an increase in the quality of teaching offered by the institution, which would greatly benefit the entire community.